Segurança alimentar e nutricional de crianças do semi-árido brasileiro e sua relação socioeconômica e de saúde - Rocha, Elida Mara Braga (2011)
The prevalence of food insecurity (FI) are more significant in the North and Northeast than in the rest of Brazil, demonstrating the stagnation of the historical regional inequalities. The semi-arid stands out for evidencing the more unfavorable life conditions. Thus, the objective of this research was to evaluate the food security situation of children under five years old, resident in the municipality of Crato, Cariri region of the state of Ceara. It was analyzed socioeconomic, demographic, health assistance and nutritional situation data through a precodified questionnaire and the food security situation applying the Food Insecurity Brazilian Scale (EBIA). The research had a transversal design, with probabilistic cluster sampling. The sample unities, in first place, were the Health Basic Unities, obtained by simple random drawing. In second place, it involved the children that were vaccinated in the D Day of the second phase of the National Immunization Campaign, in august 14th of 2010, by systematic sampling. It was performed the association among the socioeconomic, health and nutrition conditions with the food insecurity through Chi-Square test (c2), setting p<0.05. The odds ratio (OR), with confident interval of 95% and respective p values were calculated to the multiple logistic regression, since the risk factor analysis to FI. The results are referent to 370 children s responsibles, demonstrating that 58.1% of families were in FI, being 33.2% with low FI. In rural areas, the odds ratio were higher than in urban area (OR = 2.2), however the gravity of FI was higher in the urban area (7.9%) with p<0.05. The low scholarity conditions and the non white race of the responsible, the low per capita income, the low social classification, the using of the social benefits, the elevated numbers of residents and children under fiver years old per home were significant associated with FI. The logistic regression pointed as indicator of higher impact to FI: the socioeconomic level, the familiar income per capita; the level of health assistance, the visit of the Health Community Agent and the Family and Health Strategic cover, prenatal with insufficient number of consults and lack of nutritional education; and, in the level of morbidity, it there is the occurrence of fever and cough in the last 15 days. There was not association of malnutrition or overweight with FI, but it was observed the high prevalence of overweight over malnutrition, characterizing rapid nutritional transition also presented in this region. Therefore, the EBIA proved itself as indicator of the social vulnerability, disassociated with nutritional disturbs. Nevertheless, it is perceived the necessity of programs directed to nutritional education of these families and the adequacy of social and health actions to the population with FI.